Application of dynamic optimization techniques for poly(b̃- hydroxybutyrate) production in a fed-batch bioreactor - Lopez Jimenez, Jimmy Andres (2010)
Poly(b̃-hydroxybutyrate), PHB, is a microbial biopolymer produced by bacteria under unbalanced culture conditions. Such unbalanced conditions can be easily reached in a fed-batch bioreactor; therefore, it is important to know the system's behavior as well as its constraints to induce unbalanced conditions that allow the optimization of feeding profiles and, consequently, PHB productivity. In this work, dynamic optimization has been applied to maximize PHB productivity in a fed-batch bioreactor. Optimal feeding profiles of carbon and nitrogen sources, as well as their respective concentrations, were obtained using gPROMS (generalized process modeling system). When there is reliable bioreaction kinetics available, dynamic optimization becomes a very valuable tool for predicting optimal operating conditions to maximize PHB productivity, with a considerable reduction in time and experimental costs.